(untitled) (Economics and region, 2025)
The article is devoted to a comprehensive analysis of the implementation of the principles of sustainable development in tour operator activities with an emphasis on the combination of recreational tourism and local history routes. The work substantiates that the modern tourism industry is at the stage of transformation, where environmental responsibility, social awareness and economic balance become key conditions for the competitiveness of tourism enterprises. Special attention is paid to the role of tour operators as the main shapers of the tourist product, able to influence the consumption patterns of tourist services and contribute to the preservation of the recreational and cultural potential of the regions. The article examines the theoretical foundations of sustainable development and practical mechanisms of their integration into tourism activities. It is shown that recreational tourism in combination with local history routes forms a unique tourist product that contributes to the restoration of the physical and emotional state of tourists, while ensuring the preservation of natural landscapes, objects of cultural heritage and historical memory of the territories. The article emphasizes that the synergy of recreational tourism and local history routes is a promising direction for the formation of responsible tourism that meets modern global challenges and contributes to the harmonious development of territories.